East Kalimantan Program - Herman Darman (Berita Sedimentologi, 2011)
The East Kalimantan Programme (EKP) aims to enhance and support long term scientific cooperation in coastal zone research between research groups from Indonesia and the Netherlands.The Research Cluster: "Upsetting the balance in the Mahakam Delta : past, present and future impacts of sea-level rise, climate change, upstream controls and human intervention on sediment and mangrove dynamics" is one of the clusters that is funded within the EKP programme.